Fragmentation of Mansurov granite under quasi-static compression (Fracture and Structural Integrity, 2017)
The fragmentation statistics was studied in the quasi-static compression experiments conducted on prismatic specimens of Mansurov granite. The statistical analysis showed that the cumulative fragment mass distribution for granite specimens is well described by a power law function, but the fragment number-sieve size distribution deviates from the power law in the range of are equal to about 1 mm. In order to explain this fact, we investigated the structure of fractured material (Computed Tomography and microstructures study in thin sections). A sharp increase the number of grains in the range of size from to 0.5 mm to 1 mm and a change in the fragment shape (from splinter to oval) allow us to suppose that there is an addition fracture mechanism associated with disintegration of feldspar and amphiboles grains.
Keywords: Fragmentation statistics; Granite fracture; Power law distribution